2021
DOI: 10.3390/coatings11010077
|View full text |Cite
|
Sign up to set email alerts
|

Different Approaches to Low-Wettable Materials for Freezing Environments: Design, Performance and Durability

Abstract: Ice nucleation and accretion leads to multiple problems such as freezing of the streets which can cause traffic collisions or people injuries, and collapse of high voltage power lines leading to black-out and icing of aircraft components, causing major aeronautic accidents. The most widespread strategies for the removal of accumulated ice layers result in most cases being expensive, time-consuming and hazardous for the environment. In this work we present the design of hydrophobic hybrid inorganic-organic coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The authors explained the findings based on the Dzyaloshinskii-Lifshitz-Pitaevskii model. They concluded that stronger Van der Waals forces in the alumina-based SLIPS led to stronger capillarity and better self-recovery in comparison to the silica-based SLIPS [119]. As can be seen, a hierarchical structure helps in both lubricant retention and re-distribution.…”
Section: Surface Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The authors explained the findings based on the Dzyaloshinskii-Lifshitz-Pitaevskii model. They concluded that stronger Van der Waals forces in the alumina-based SLIPS led to stronger capillarity and better self-recovery in comparison to the silica-based SLIPS [119]. As can be seen, a hierarchical structure helps in both lubricant retention and re-distribution.…”
Section: Surface Structurementioning
confidence: 99%
“…Hierarchical nanostructures produced higher capillary pressure within nanopores, which locked the lubricant more effectively within the nanostructures and led to a significant improvement in the durability of the surface. Boveri et al [119] used the sol-gel method to fabricate SLIPS with alumina and silica nanoparticles, resulting in a hierarchical structure with an organic coating. Fluorinated Krytox oil was chosen as the lubricant for its high repellency and exceptional durability below the freezing point.…”
Section: Surface Structurementioning
confidence: 99%
“…The problems related to ice adhesion on structures is a global annoyance which has caused and is still causing threat to industry and public safety in many parts of the world, including North American (USA, Canada), Asian (Japan, China) European and Scandinavian countries, as reflected by the research contributions in this Special Issue by authors from these countries who constantly strive to minimize its impacts [1][2][3][4][5][6][7][8][9][10]. World renowned experts have been addressing the ice adhesion issues with their advanced research and development and in the finding of advanced technologies to evaluate the adhesion phenomena, both theoretically and experimentally.…”
mentioning
confidence: 99%
“…The ten contributions constituting this Special Issue are composed of the latest developments and the state of the art regarding ice adhesion, which are well elaborated for a wide range of readers, including research scientists, students and industrials, as well as the curious audience. These ten contributions originate from countries worldwide, namely, Canada (Quebec), Italy, Spain, China, Norway, Germany, Bulgaria and USA [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation